Nanoclay as Adsorbent: Evaluation for Removing Dyes Used in the Textile Industry - Martínez Stagnaro, Susana Yamila (2015)
The dyes commonly used in the textile industry have structural resonant valence distribution, within a complex molecule, which determines the color of the dyes. The coloring is produced by chromospheres holding radiation in UV-visible range. Besides coloring, these compounds can be found in waste water and cause serious problems in living organisms, because their biodegradation products may be a source of toxic substances such as amines, which are generated from the characteristic azo chromospheres groups in most of the dyes. Current treatments for color removal from hazardous waste from these materials are complex and costly, for this reason some industries do not treat the wastes generated during the staining step. The aim of this study is to evaluate the use of nanoclay as adsorbents for dye used in the textile industry. The dyes used in this work are commercially known as: Orange GR, Black GN an African Brown. Nanoclay was obtained by bentonite treated with organic cation. The retention of the dye was evaluated by measurements in the UV-visible spectrum by using a HP-8354 equipment.